Gas-controlled heat pipes in metrology: More than 30 years of technical and scientific progresses. (November 2020) - Merlone, A.; Coppa, G.; Bassani, C.; Bonnier, G.; Bertiglia, F.; Dedyulin, S.; Favreau, J-O.; Fernicola, V.; van Geel, J.; Georgin, E.; Gotoh, M.; Krenek, S.; et al.
Abstract: Gas-Controlled Heat Pipes (GCHPs) are devices based on generating and maintaining, at millikelvin level, a thermodynamic liquid-vapour equilibrium of a fluid. For this reason, GCHPs have been studied for more than thirty years for research and applications in thermal metrology. Capabilities have been constantly improved and adapted by National Metrology Institutes (NMIs) and accredited laboratories. Activities include study of vapour pressure curves of pure elements and substances, thermometers' non-uniqueness up to 960 °C, calibrations between −20 °C and 900 °C with millikelvin uncertainties, studies of innovative pressure controllers allowing regulation better than 10 −6 from below 1000 Pa up to 400 kPa. GCHPs operating at different temperature ranges have also been connected to a common pressure line in the so-called "Temperature Amplifier" configuration. This review paper presents an almost complete report about the several models of GCHPs, materials and working fluids, techniques adopted in different temperature/pressure ranges. All involved NMIs using GCHP are here included, with detailed bibliography.